A day of judgment - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels, 2026)
Inspector Ian Rutledge of Scotland Yard travels to England's windswept coastline to investigate a murder in a place where, several years after the end of WWI, the memory of the war still runs strong.